PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA PEGAWAI DINAS PERTANIAN KOTA KENDARI - Murniati Muhtar; Nasrul Nasrul; Sriwiyati Mahrani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This study aims to determine and analyze the influence of Organizational Culture, Organizational Commitment and Organizational Citizenship Behavior (OCB) on Kendari City Agricultural Service Employee Performance. This study uses a quantitative approach and is explanatory in nature, which aims to determine the factors/influences of the composition of a variable. The object of this research is the employees of the Kendari City Agriculture Service with a saturated sample of all employees, as many as 76 respondents. The analysis technique used is a quantitative method, namely multiple linear regression analysis.The results of this study indicate that there is a positive and significant influence between organizational culture, organizational commitment, and organizational citezenship behavior on the performance of the Kendari City Agriculture Office employees. The direction of positive influence shows that the more organizational culture of organizational commitment, and organizational citezenship behavior perceived by members of the organization, the higher the performance of these employees..